Simple flash screens for shaped charge jet and flyer velocity measurements - Künzel, Martin; Kučera, Jindřich; Kvapil, Jan; Pachman, Jiří (My University, 2021)
The paper describes a novel technique for measuring the velocity of fast flying objects. The technique utilises a series of simple single-use screens which are placed along the expected flight path. The projectile interaction with the screen generates a flash of light which is captured by an optical fibre connected to the light detecting device. The velocities are calculated from the signal arrival times and screen positions. The flash screens were tested using copper shaped charge jets and flyer discs accelerated by explosive charges made of sensitised nitromethane. In addition to the simple time of arrival measurement with VOD-815, the light signals were recorded using an OPTIMEX-64 light analyser which enabled checking their intensity and reproducibility. Some of the experiments were also carried out using a UHSi 12/24 high-speed camera. The flyer plate velocities measured were compared with empirical calculations from a Gurney model.
Jednoduché zábleskové brány pro měření rychlosti letících projektilů a kumulačního paprsku
Keywords: fibre optics; shaped charge; jet velocity; flyer plate; vláknová optika; kumulativní nálož; rychlost kumulačního paprsku; urychlovaný projektil